Assessing factors influencing internet banking adoption by using rasch model measurement - Khairi Azhar Aziz; Marzanah A. Jabar; Salfarina Abdullah; Rozi Nor Haizan Nor (Bulletin of Electrical Engineering and Informatics, 2022)
The purpose of this paper is to use the Rasch model software in analyzing the identified influencing factors of internet banking towards improving adoption usage and to find the validity and reliability of the instrument. An initial conceptual model was developed based on the previous of Literature Review. About 17 factors have been identified from the previous models and frameworks and they have been improved as influencing factors. Those factors are the website design (WD), the ease of use (EOU), the security, the quality system, the social influence, the trust, the electronic word of mouth (eWOM), the rewards, the perceived usefulness (PU), the perceived ease of use (PEOU), the intention to use (IU), the sustainability, the commitment, the user experience/generation, the knowledge, the profession, and the income. The questionnaire survey was successfully conducted with 51 respondents and pilot data verification of 30 respondents. The results showed that person reliability was 0.93 spread of person respondent was 54.06 and person separation was 3.66 However, item reliability result was 0.88, spread of item was 45.98 and item separation equal to 2.70 was fair. This paper was proven to be a significant contribution to the validity and reliability of using the Rasch model.